Evaluasi efektivitas kurikulum merdeka dalam meningkatkan karakter dan kompetensi siswa di sekolah dasar - Nurul Fatimah; Adika Agil Firdaus; Dewi Fitri Yanti; Mohamad Teguh Baktiar; Natasya Zulfa; Putri Fasya Naziha; Zakia Valerina; Afridha Laily Alindra (Didaktika Dwija Indria, 2025)
This article aims to examine the effectiveness of implementing Merdeka Curriculum in improving student character at SDN 6 Nagrikaler. This research uses a descriptive qualitative method conducted through observation, interviews with the principal, and documentation analysis. Data were collected through observation, interviews with the principal, and documentation. The results showed that the implementation of Merdeka Curriculum significantly improved students' character in the aspects of responsibility, honesty, tolerance, confidence, caring, cooperation, discipline, independence, and integrity. The student-centered and project-based learning approach plays an important role in internalizing the values of the Pancasila Student Profile. Although there are still challenges in synchronizing the environment, the research concludes that Merdeka Curriculum is effective in shaping students' holistic character, with recommendations for developing relevant and collaborative learning strategies.